India's revolutionary inheritance : politics and the promise of Bhagat Singh - Moffat, Chris (Cambridge University Press, 2019)
"What do anti-colonial histories mean for politics in contemporary India? How can we understand a political terrain that appears crowded with the dead, heroic figures from past struggles who call the living to account and demand action? What role do these 'afterlives' play in the inauguration of new politics and the fashioning of possible futures? In this engaging and innovative analysis of anti-colonial afterlives in modern South Asia, Chris Moffat crafts a framework that takes the dead seriously - not as passive entities, ceremonially invoked, but as active interlocutors and instigators in the present. Focusing on the iconic revolutionary martyr Bhagat Singh (1907-1931), Moffat establishes the problem of inheritance as central to the forms and futures of democracy in this postcolonial polity. Tracing Bhagat Singh's revenant presence in India today, he demonstrates how living communities are animated by a sense of obligation, duty or debt to the dead"--